Azimuthal asymmetry in the risetime of the Surface Detector signals of the Pierre Auger Observatory - Allekotte, Ingomar (2016)
The azimuthal asymmetry in the risetime of signals in Auger surface detector stations is a source of information on shower development. The azimuthal asymmetry is due to a combination of the longitudinal evolution of the shower and geometrical effects related to the angles of incidence of the particles into the detectors. The magnitude of the effect depends upon the zenith angle and state of development of the shower and thus provides a novel observable, ðsec θÞmax, sensitive to the mass composition of cosmic rays above 3 × 1018 eV. By comparing measurements with predictions from shower simulations, we find for both of our adopted models of hadronic physics (QGSJETII-04 and EPOS-LHC) an indication that the mean cosmic-ray mass increases slowly with energy, as has been inferred from other studies. However, the mass estimates are dependent on the shower model and on the range of distance from the shower core selected. Thus the method has uncovered further deficiencies in our understanding of shower modeling that must be resolved before the mass composition can be inferred from ðsec θÞmax.